Recovery of Biomolecules by Nanofiltration Membranes - Turpo Huanca, Liliana E. (2018)
IN THIS WORK, THE RECOVERY OF BIOMOLECULES THROUGH NANOFILTRATION MEMBRANES WILL BE STUDIED, SINCE BIOMOLECULES ARE COMPLEX ORGANIC MOLECULES. THE WORK WILL CONSIST OF TWO MAIN PARTS, THE FIRST PART CONSISTS OF THE BIBLIOGRAPHIC REVIEW OF SCIENTIFIC STUDIES IN WHICH THE APPLICATION OF NANOFILTRATION MEMBRANE TECHNOLOGY FOR THE SEPARATION OF AMINO ACIDS AND PEPTIDES, PUBLISHED IN HIGH IMPACT JOURNALS AND THE SECOND PART CONSISTS OF AN EXPERIMENTAL WORK, WHICH WAS PERFORMED WITH A PEPTIDE THAT IS TRIGLYCINE, SAID PEPTIDE WAS WORKED BOTH IN A SOLUTION OF DEIONIZED WATER, AND IN A SOLUTION IN WHICH A CONCENTRATION OF SODIUM CHLORIDE WAS ADDED.